Rural/urban dwelling across the life-course and late-life cognitive ability in Mexico. (March 2022) - Saenz, Joseph L.; Downer, Brian; Garcia, Marc A.; Wong, Rebeca
Abstract: Background: Urban advantages in older adults' cognitive function have been observed. Less is known about early-life urban dwelling and late-life cognition. We evaluate how rural/urban dwelling throughout life and rural to urban shifts in life relate with cognition in Mexico, a country experiencing aging and urbanization. Methods: Data came from the 2003 and 2012 Mexican Health and Aging Study (n = 12, 238 adults age 50+). Early-life urban dwelling was self-reported. Late-life urban dwelling was based on population size of respondents' community of residence (community 2500+ people) at the time of survey. Cognitive function was measured across several cognitive tasks. We assess differences in baseline cognitive function and nine-year decline across groups using a latent change score model. Results: Cross-sectionally, compared to always rural dwellers, rural-urban transitions were associated with cognitive benefits, though individuals residing in urban areas continuously through life exhibited the highest levels of cognitive function ( β  = 0.89, 95% CI: 0.83, 0.96) even after adjusting for SES, health, and health behaviors ( β  = 0.28, 95% CI: 0.22, 0.35). Longitudinally, always urban dwellers exhibited slower decline than always rural dwellers when adjusting for baseline cognition ( β  = 0.11, 95% CI: 0.03, 0.18), though faster decline when baseline cognition was not adjusted ( β  = −0.11, 95% CI: -0.18, −0.04). No differences were observed for cognitive change across comparison groups after adjusting for potential mechanisms. Conclusions: Early- and late-life urban dwelling may result in cognitive advantages for older Mexican adults. Clinicians should consider where individuals resided throughout life to better understand a patient's likelihood of experiencing poor cognitive outcomes. Highlights: Urban dwelling in early- or late-life was associated with better late-life cognitive ability in Mexico. Always-urban dwellers had the highest level of cognitive ability. Compared to always-rural dwellers, rural-to-urban transition in life was associated with better cognitive ability in old age. Always-urban differed from always-rural dwellers in their pace of cognitive decline depending on baseline controls.